Van der Waals Nanowires with Continuously Variable Interlayer Twist and Twist Homojunctions. (3rd December 2020) - Sutter, Peter; Idrobo, Juan‐Carlos; Sutter, Eli
Abstract: Moiré patterns at van der Waals interfaces between twisted 2D crystals give rise to distinct optoelectronic excitations, as well as, narrowly dispersive bands responsible for correlated electron phenomena. Contrasting with the conventional, mechanically stacked planar twist moirés, recent work shows twisted van der Waals interfaces spontaneously formed in nanowires of layered crystals, where Eshelby twist due to axial screw dislocations stabilizes a chiral structure with small interlayer rotation. Here, the realization of tunable twist in germanium(II) sulfide (GeS) van der Waals nanowires is reported. Tapered nanowires host continuously variable interlayer twist. Homojunctions between dislocated (chiral) and defect‐free (achiral) segments are obtained by triggering the emission of axial dislocations during growth. Measurements across such junctions, implemented here using local absorption and luminescence spectroscopy, provide a convenient tool for detecting twist effects. The results identify a versatile system for 3D twistronics, probing moiré physics, and for realizing moiré architectures without equivalent in planar systems. Abstract : Eshelby twist in van der Waals nanowires creates twisted interfaces and associated moiré patterns that modulate the electronic structure and can cause correlated electron phenomena. Here, twist manipulation is demonstrated by realizing nanowires harboring continuously varying interlayer moirés and homojunctions connecting twisted and equilibrium‐stacked segments. These novel architectures provide versatile platforms for exploring twist effects in van der Waals crystals.